EFEK STRATEGI DIVERSIFIKASI PRODUK DAN JASA TERHADAP PERTAMBAHAN PENUMPANG PADA JALUR UTAMA TRANSPORTASI - Prayitno Prayitno; Hesti Widianti (Pusat Penelitian dan Pengabdian Masyarakat Politeknik Harapan Bersama, 2018)
Descriptive research is used to gain insight into the size of product diversification, service quality and the perceived availability of consumers offered by transportation equipment entrepreneurs in relation to the service quality model perceived by Gronroos (1994) to develop as a functional and technical quality dimension. Bus Entrepreneurs can provide the desired means of transportation by passengers supported by toll lines that operate along the main line to be a great opportunity for Bus entrepreneurs, product diversification means that reducing seat seats to be the ultimate choice that should be done by Bus entrepreneurs so that the clarity of departure can obtained by passengers and good service becomes a supporting factor in addition to the existence / ease of getting Bus transportation